Revitalisasi Nilai Pancasila sebagai Basis Moderasi Beragama pada Masyarakat Multikultural - royyan, fahmi ilham (Maliki Interdisciplinary Journal, 2026)
Indonesia has a very wide diversity of religions, cultures, ethnicities, and languages, so the management of diversity is crucial to maintain a balance of social life. If differences are not handled properly, society is vulnerable to friction, the emergence of intolerance, and the development of radical ideologies—especially in the era of globalization when transnational ideologies are increasingly easily influencing the religious perception of the younger generation. In such conditions, religious moderation plays an approach that helps people build religious attitudes that are more proportionate, not excessive, and remain in harmony with human values. Pancasila as the foundation of the state has contained moderate values that emphasize inclusivity, respect for human dignity, and strengthening unity. Each precept provides a moral and philosophical basis for fostering peaceful and tolerant religious practices in a pluralistic society. Therefore, the re-strengthening of Pancasila values is an important step to strengthen religious moderation, prevent social division, and build a balanced, civilized, and religious life in accordance with the diverse character of the nation.